Influence of irradiation and addition of antioxidants on the oxidation stability of Jatropha, Pongamia and Tectona Grandis biodiesels. Issue 1 (31st December 2022) - Singh, Meetu; Sharma, Neerja; Sarin, Amit; Kesharvani, Sujeet; Tiwari, Chandrabhushan; Verma, Tikendra Nath; Dwivedi, Gaurav
Abstract : Biodiesel is chemically an ester molecule; there is every possibility that in the presence of air or oxygen, it will be hydrolysed to alcohol and acid. The oxidation of the biodiesels in an ambient air environment leads to deterioration, which diminishes their prospects as mainstream fuel due to their lesser strength against oxidation. The present work reports the oxidation stability of Jatropha biodiesel and Pongamia biodiesel when exposed to sunlight and ultraviolet (UV) irradiation for up to 10 h and 30 days, respectively. The experimentation was further extended with novel biodiesel, Tectona Grandis biodiesel. The different synthetic antioxidants: Butylated hydroxyanisole, Butylated hydroxytoluene, and Tert-butyl hydroquinone (TBHQ) were added to the biodiesel to observe their impact along with varying storage ambiance. The experimental results reveal that exposure to UV and sunlight prompted the oxidation process and the addition of antioxidants is functional to beat the negative influence of irradiation.